Proteomic Profile Associated With Loss of Spontaneous Human Immunodeficiency Virus Type 1 Elite Control. (12th October 2018) - Rodríguez-Gallego, Esther; Tarancón-Diez, Laura; García, Felipe; del Romero, Jorge; Benito, Jose Miguel; Alba, Verónica; Herrero, Pol; Rull, Anna; Dominguez-Molina, Beatriz; Martinez-Madrid, Onofre; Martin-Pena, Luisa; Pulido, Federico; et al.
Abstract : Proteomic signature was associated with spontaneous loss of virological control, which is characterized by inflammation, transendothelial migration, and coagulation. This is the first "omics" approach showing potential biomarkers for the prediction of this virological progression and as therapeutic targets in elite controllers. Abstract: Background: Elite controllers (ECs) spontaneously control plasma human immunodeficiency virus type 1 (HIV-1) RNA without antiretroviral therapy. However, 25% lose virological control over time. The aim of this work was to study the proteomic profile that preceded this loss of virological control to identify potential biomarkers. Methods: Plasma samples from ECs who spontaneously lost virological control (transient controllers [TCs]), at 2 years and 1 year before the loss of control, were compared with a control group of ECs who persistently maintained virological control during the same follow-up period (persistent controllers [PCs]). Comparative plasma shotgun proteomics was performed with tandem mass tag (TMT) isobaric tag labeling and nanoflow liquid chromatography coupled to Orbitrap mass spectrometry. Results: Eighteen proteins exhibited differences comparing PC and preloss TC timepoints. These proteins were involved in proinflammatory mechanisms, and some of them play a role in HIV-1 replication and pathogenesis and interact with structural viral proteins. Coagulation factor XI, α-1-antichymotrypsin, ficolin-2, 14-3-3 protein, and galectin-3-binding protein were considered potential biomarkers. Conclusions: The proteomic signature associated with the spontaneous loss of virological control was characterized by higher levels of inflammation, transendothelial migration, and coagulation. Galectin-3 binding protein could be considered as potential biomarker for the prediction of virological progression and as therapeutic target in ECs.